Nutritional Status, Physical Activity, Oxidative Stress, and Cognitive Function in Pre Elderly and Elderly - Dainy, Nunung Cipta; Kusharto, Clara Meliyanti; Madanijah, Siti; Nasrun, Martina Wiwie Setiawan; Turana, Yuda (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
This study aimed to analyse the relation of nutritional status, physical activity or oxidative stress with cognitive function of pre-elderly and elderly. A comparative cross-sectional study was conducted on 40 pre-elderly and 35 elderly subjects who were admitted to the Integrated Development Post Program (Posbindu) between September 2014 and January 2015. Anthropometric measurements (weight and height), physical activity, and biochemical data (oxidized low-density lipoprotein[Ox-LDL] and serum malondialdehyd [MDA]) were obtained. Nutritional status was assessed through body mass index (BMI), while the cognitive function was measured by Rey Osterrieth Complex Figure (ROCF) and Digit Span Backward. The data were analysed using an independent t-test and Spearman’s test with a confidence level of 95%. The study showed that the prevalence of malnutrition among the pre-elderly and elderly were 60.0% and 80.0%, respectively. Concerning physical activity, those who belonged to inactive-sedentary activity based on physical activity level (PAL) ratio were 55.0% and 45.7%, respectively. There were no significant differences in Ox-LDL, MDA levels and cognitive function (p>0.05). Significant negative correlations existed between Ox-LDL and immediate visual memory function (r=-0.289; p<0.05), as well as between Ox-LDL and delayed visual memory function (r=-0.288; p<0.05). The conclusion that visual memory function was only correlated with Ox-LDL.